2016
DOI: 10.3402/fnr.v60.32697
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption pattern among adults of different ethnics in Peninsular Malaysia

Abstract: BackgroundUnderstanding different patterns of fish consumption is an important component for risk assessment of contaminants in fish. A few studies on food consumption had been conducted in Malaysia, but none of them focused specifically on fish consumption. The objectives of this study were to document the meal pattern among three major ethnics in Malaysia with respect to fish/seafood consumption, identify most frequently consumed fish and cooking method, and examine the influence of demographic factors on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 26 publications
2
42
0
1
Order By: Relevance
“…A study showed Malays possessed highest fish intake as compared to other ethnics. This finding was in line with the study that Malaysians consumed 168 g/day fish, with Malays' consumption of fish (175±143 g/day) significantly (p < 0.001) higher compared with the other two ethnic groups (Chinese = 152±133 g/day, Indians = 136±141 g/day) (Ahmad et al, 2016).…”
Section: Based Onsupporting
confidence: 91%
“…A study showed Malays possessed highest fish intake as compared to other ethnics. This finding was in line with the study that Malaysians consumed 168 g/day fish, with Malays' consumption of fish (175±143 g/day) significantly (p < 0.001) higher compared with the other two ethnic groups (Chinese = 152±133 g/day, Indians = 136±141 g/day) (Ahmad et al, 2016).…”
Section: Based Onsupporting
confidence: 91%
“…The low calcium intake of Indian respondents was mainly due to less calcium-rich food consumption such as milk, dairy products and also fish, as reported in their three days food record. Moreover, the survey found that consumption of fish among Malays was significantly higher compared with the Chinese and Indian ethnic groups (Ahmad et al, 2016). Hence, based on supporting findings from the previous study, it can still be concluded that Indians might not consume an adequate amount of calcium and vitamin D compared with other major ethnicities in Malaysia.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, even though Table 4 shows that significant ethnic differences in vitamin D intake (p< 0.05), these differences actually without association with their ethnicity. A previous study found that fish consumption patterns were significantly associated with ethnicity (Ahmad et al, 2016). Therefore, the differences in vitamin D intake among respondents might be due to the difference in fish consumption pattern.…”
Section: Discussionmentioning
confidence: 92%
“…A study on infant weaning practices found that infants in Vietnam and China were introduced to solid foods earlier than Australian infants and that rice porridge and cereal were used as the infants’ first foods in most Asia‐Pacific countries although it is still unclear whether these differences contribute to food allergy risk . The average shellfish consumption in Malaysian adults was around 100 g/person per day, which is much higher than reported in US adults (22 g/person per day) although there is currently no clear evidence linking volume of shellfish allergen consumption to the development of shellfish allergy.…”
Section: Asian Epidemiology On Food Allergy and Timing Of Introductiomentioning
confidence: 99%